Interface and properties of inorganic fullerene tungsten sulphide nanoparticle reinforced poly (ether ether ketone) nanocomposites - Nannan Wang; Zhuxian Yang; Yuan Wang; Kunyapat Thummavichai; Yongde Xia; Oana Ghita; Yanqiu Zhu (Results in Physics, 2017)
We report a simple and effective method to fabricate PEEK (poly ether ether ketone)/IF-WS2 (Inorganic Fullerene Tungsten Sulphide) nanocomposites with IF-WS2 content up to 8 wt%. We have used electron microscopies to characterise the morphology and structural features of the nancomposites, and FTIR and XPS to show that some chemical interface bondings were formed between the PEEK and IF-WS2. We demonstrate that the resulting PEEK/IF-WS2 nanocomposites showed an extraordinary 190% increase in thermal conductivity, 50 °C higher in degradation temperature, and mild improvements in strength and hardness. The increased degradation activation energy from 64 to 76 kJ/mol for neat PEEK and PEEK/IF-WS2 nanocomposites, respectively, is attributed to the synergistic interface between the PEEK matrix and IF-WS2 nanoparticles. The enhancements in both the mechanical and thermal properties will significantly expand the capacities of PEEK-based nanocomposites towards applications where thermal conductivity and stability are important. Keywords: Nanocomposites, PEEK, IF-WS2, Interface, Thermal conductivity